Research of Road Equipment Needs and Safety Management Using the School Safety Zone (ZOSS) Concept on I Gusti Ngurah Rai Road in Palu City - Randy Bramesta Putra Pratama; Taslim Bahar; Arief Setiawan (PT Publikasiku Academic Solution, 2025)
The School Safety Zone (ZoSS) is a government-initiated program designed to regulate vehicle speed in school areas through time-based speed zones, ensuring pedestrian safety, particularly for students. The implementation of ZoSS aims to reduce traffic accidents by requiring vehicles to drive at low speeds when entering school zones, anticipating unpredictable pedestrian movements. This research analyzes the need for School Safety Zone (ZoSS) facilities along the I Gusti Ngurah Rai Road segment, particularly in the South Tatura Education Area, using the Regulation of the Director General of Land Transportation No: SK.3236/AJ.403/DRJD/2006 as a reference. Data analysis was conducted using normal distribution statistics (Z-test) by comparing the calculated Z-value with the Z-table value for pedestrian behavior, drop-off/pick-up behavior, and vehicle speeds in the area. Additionally, the analysis included the need for drop-off/pick-up zones and pedestrian infrastructure to facilitate safe student activities. The results indicate that the South Tatura Education Area is not yet safe, confirming the need for a ZoSS in the area. The proposed ZoSS design is 2/2UD-25, with a two-lane undivided road (2/2-TT), stopping sight distance of 50–85 meters, school zone speed limit of 25 km/h, and a zone length of 150 meters. The required ZoSS facilities include School Safety Zone markings, zebra crossings, traffic signs, yellow zigzag road markings, crossing guides, and additional facilities such as rumble strips.